Decrease in RNA Folding Cooperativity by Deliberate Population of Intermediates in RNA G‐Quadruplexes1. Issue 2 (20th November 2012) - Kwok, Chun Kit; Sherlock, Madeline E.; Bevilacqua, Philip C.
<x xml:space="preserve">Abstract</x> Keeping a broad (RNA) perspective: Conventional biochemical detection systems only have a 100‐fold linear response range. The range of potassium concentrations detected by an RNA G‐quadruplex sequence can be broadened by intentionally populating multiple intermediate folding states (see scheme). The folding of the RNA G‐quadruplexes was monitored by both circular dichroism and intrinsic fluorescence spectroscopy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>